BANKIERZY PUBLICZNI W ŹRÓDŁACH PRAWA RZYMSKIEGO - Niczyporuk, Piotr (Zeszyty Prawnicze, 2016)
PUBLIC BANKERS IN ROMAN LAW SOURCES Summary The Romans had an extensive terminology for persons who engaged in banking activities; however, only nummularii and mensarii pursued activities on behalf of the State. Their operations may be regarded as public banking in the broad sense of the term, and were conducted from the 4th century BC until the 3rd century AD. Banking was of key importance in the peak period of growth for Roman trading and financial operations, and this is confirmed in the sources for Roman law. We do not have any records for the bankers referred to as nummularii until the period of classical Roman law, when we get fragmentary references to them in the writings of Roman jurists. There are only two passages on their public activities in the quality control and exchange of coinage; the first is by Sextus Caecilius Africanus, and the second is Ulpian’s commentary on the duties of the prefectus Urbi. Other references to them in the works of Roman jurists relate to their operations concerning deposits and credit, and as such do not belong to the sphere of public law. We get more mentions of public bankers in the Roman non-legal literature. Mensarii, who performed a certain type of public banking duties, are referred to in Livy’s Ab urbe condita. Cicero, Suetonius, and Festus also wrote about them. Moreover, Grammaticus treated the term mensarii as synonymous with nummularii. Presumably the two categories of public bankers were considered to be generally respected individuals. We also have mentions of the nummularii in the non-legal literature. In his Satyricon Petronius esteemed their skills of assessing the quality of coins; they were also held in high regard by Martial, Suetonius, and Apuleius. Suetonius wrote of the severe penalties imposed on the nummularii by the Emperor Galba. On the other hand, all we get in the epigraphic sources, mostly tombstone inscriptions from Rome, elsewhere in Italy, and the western provinces, are records of the activities of the nummularii for the quality control and exchange of coinage, considered an important duty from the point of view of the State. In fact the non-legal and epigraphic literature of Rome tells us more about public bankers than do the sources on Roman law. Their work did not give rise to many legal problems, as we may conclude from the fact they are mentioned only in two juridical passages. The assessment of the quality of coins and their exchange, and other banking activities on behalf of the State were sufficiently supervised by Roman administrative officers, so there was no need for jurists to comment on them at length.